Bengbu City’s Parking: A Policy (Re)Design Project - Yang, Xiangqian; Wang, Haolin; Wang, Jingjing; Wu, Huaming; Ma, Guoxin (INTI International University, 2020)
In developed countries, parking has been a widespread problem for a long time. In China, its growing population has put its public transportation system under a lot of pressure, with the increasing car ownership in its big and small cities expanding the size of urban centres which in turn increases the demand for faster movement and mobility. As researchers based in Bengbu, a city in Anhui province, China, we observe that presently the phenomenon of disorderly parking and traffic congestion on urban roads is serious in the city. Recruited by the local government, we propose a project on policy (re)designing for Bengbu’s on-street parking in particular, and parking management in general. This paper provides a background and positioning of the proposed project, summarising its viewpoints and recommendations for policy-making.